2008
DOI: 10.1128/aem.00061-08
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Metalloprotease ofVibrio tubiashiiIs a Major Virulence Factor for Pacific Oyster (Crassostrea gigas) Larvae

Abstract: Vibrio tubiashii is a recently reemerging pathogen of larval bivalve mollusks, causing both toxigenic and invasive disease. Marine Vibrio spp. produce an array of extracellular products as potential pathogenicity factors. Culture supernatants of V. tubiashii have been shown to be toxic to oyster larvae and were reported to contain a metalloprotease and a cytolysin/hemolysin. However, the structural genes responsible for these proteins have yet to be identified, and it is uncertain which extracellular products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
131
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(137 citation statements)
references
References 49 publications
4
131
0
Order By: Relevance
“…In V. tubiashii, the zinc-metalloprotease VtpA regulates VthA hemolysin expression by means of a posttranscriptional mechanism (Hasegawa and Häse, 2009). The VtpA mutant of V. tubiashii had decreased pathogenic potential in C. gigas larvae (Hasegawa et al, 2008). The hyper expression of VthA did not increase the pathogenic potential of V. tubiashii in C. gigas.…”
Section: Vibrio Coralliilyticus Genome E De O Santos Et Almentioning
confidence: 93%
See 2 more Smart Citations
“…In V. tubiashii, the zinc-metalloprotease VtpA regulates VthA hemolysin expression by means of a posttranscriptional mechanism (Hasegawa and Häse, 2009). The VtpA mutant of V. tubiashii had decreased pathogenic potential in C. gigas larvae (Hasegawa et al, 2008). The hyper expression of VthA did not increase the pathogenic potential of V. tubiashii in C. gigas.…”
Section: Vibrio Coralliilyticus Genome E De O Santos Et Almentioning
confidence: 93%
“…The VcpA zinc-metalloprotease has been identified in previous studies as the key virulence factor likely important in the bacterial infection of corals and implicated in coral tissue necrosis (Ben-Haim et al, 2003a, b;Sussman et al, 2008). The V. coralliilyticus vcpA gene is orthologous to the vtpA gene from the oyster pathogen Vibrio tubiashii and similarly identified as central for strain virulence (Hasegawa et al, 2008). A DvcpA V. coralliilyticus P1 mutant demonstrated the same pathogenic potential as the wild-type strain in two animal models and a whole cell Symbiodiunium bioassay evaluated in this study, highlighting that the pathogenicity of vibrios in marine animals is a complex interplay of multiple genetic factors and unlikely the result of one determinant.…”
Section: Vibrio Coralliilyticus Genome E De O Santos Et Almentioning
confidence: 98%
See 1 more Smart Citation
“…One of the shellfish pathogenic Vibrio species, Vibrio tubiashii, is a recently reemerging pathogen of several species of bivalve larvae including oysters, clams, and geoducks (9, 10). Disease caused by V. tubiashii is characterized by a reduction in larval motility, detached vela, and necrotic soft tissue, accompanied by high mortality rates (42).Although only limited information is available about many aspects of V. tubiashii, including virulence factors produced, previous studies demonstrated that V. tubiashii strains, including RE22 and RE98, showed the highest degree of disease severity (10), with the production of high levels of extracellular metalloprotease (VtpA) and hemolysin (VthA) (7,19,25). We showed in a previous study that the purified VtpA protein caused significantly high toxicity to oyster larvae, strongly suggesting that the VtpA is a structural toxin to the host (18).…”
mentioning
confidence: 99%
“…In addition, we recently observed that the purified VtpA directly inactivates VthA hemolysin (17). Although virulence of V. tubiashii is likely multifactorial, the metalloprotease VtpA appears to be the main secreted toxin in V. tubiashii supernatants (18,19).Typically, this type of metalloprotease is tightly regulated by a TetR family of DNA-binding transcriptional regulatory proteins in a variety of Vibrio species (5,22,23,35,39). For example, in V. vulnificus a deletion of the TetR family regulator, SmcR, results in severely reduced production of the VvpE metalloprotease (22).…”
mentioning
confidence: 99%